Effects of chlorpyrifos on the gut microbiome and urine metabolome in mouse (Mus musculus). (June 2016) - Zhao, Yanping; Zhang, Yan; Wang, Guoxiang; Han, Ruiming; Xie, Xianchuan
Abstract: In this study, the toxic effects of clorpyrifos (CPF) on the gut microbiome and related urine metabolome in mouse ( Mus musculus ) were investigated. Mice were exposed to a daily dose of 1 mg kg −1 bodyweight of CPF for 30 d. As a result, CPF significantly altered the gut microbiota composition in terms of the relative abundance of key microbes. Meanwhile, CPF exposure induced the alterations of urine metabolites related to the metabolism of amino acids, energy, short-chain fatty acids (SCFAs), phenyl derivatives and bile acids. High correlations were observed between perturbed gut microbiome and altered metabolic profiles. These perturbations finally resulted in intestinal inflammation and abnormal intestinal permeability, which were also confirm by the histologic changes in colon and remarkable increase of lipopolysaccharide (LPS) and diamine oxidase (DAO) in the serum of CPF-treated mice. Our findings will provide a new perspective to reveal the mechanism of CPF toxicity. Graphical abstract: Highlights: Toxic effects of CPF on mice gut microbiome and urine metabolome were investigated. CPF changed the gut microbiota composition and metabolism related genes expression. Some gut microbiota-related metabolites were perturbed by CPF exposure.